Endovascular Approaches to the Cavernous Sinus in the Setting of Dural Arteriovenous Fistula - Dye, Justin (Brain Sci, 2020)
Dural arteriovenous fistulas involving the cavernous sinus can lead to orbital pain, vision loss and, in the setting of associated cortical venous reflux, intracranial hemorrhage. The treatment of dural arteriovenous fistulas has primarily become the role of the endovascular surgeon. The venous anatomy surrounding the cavernous sinus and venous sinus thrombosis that is often associated with these fistulas contributes to the complexity of these interventions. The current report gives a detailed description of the alternate endovascular routes to the cavernous sinus based on a single center’s experience as well as a literature review supporting each approach. A comprehensive understanding of the anatomy and approaches to the cavernous sinus available to the endovascular surgeon is vital to the successful treatment of this condition.